hub HUBUNGAN ANTARA BODY IMAGE DENGAN PENERIMAAN DIRI SISWA JURUSAN TEKNIK KOMPUTER DAN JARINGAN (TKJ) - Inten Anugraini; Yessy Elita; Anni Suprapti (Consilia : Jurnal Ilmiah Bimbingan dan Konseling, 2024)
This research aims to determine the relationship between body image and self-acceptance of students majoring in Computer and Network Engineering (TKJ). The design of this research is correlational research with data collection techniques using body image questionnaires and self-acceptance questionnaires. Data were analyzed using Pearson product moment correlation which showed a positive relationship between body image and student self-acceptance with a value of 0.324. This means that there is a relationship between body image and self-acceptance, that the more positive the body image, the better the self-acceptance of students majoring in Computer and Network Engineering (TKJ) at SMK Negeri 3 Bengkulu City. Keywords: body image, self-acceptance, students